PERAN GENERASI PESONA INDONESIA DALAM PENGEMBANGAN PARIWISATA DI JAWA TENGAH DENGAN PERSPEKTIF COMMUNITY DEVELOPMENT - Maulana, Muhammad Yahya; ., Sulistyowati (Journal of Politic and Government Studies, 2018)
Generasi Pesona Indonesia (GenPI) is a community that was inaugurated by the Ministry of Tourism, Republic of Indonesia. This community stands as an effort in the development of Indonesian tourism, especially in tourism promotion.  GenPI is spread in 22 provinces, one of them is in Central Java. Central Java has 511 destinations in 35districts/cities. However, the amount of tourism potential can cause problems in terms of tourism marketing that is not evenly distributed. This is due to the the inability of the Central Java government to market these tourist destinations.This research aims to find out and analyze the role of GenPI Central Java in developing Central Java tourism as seen from the perspective of community development and how the forms of coordination are created between GenPI, government and society in developing tourism in Central Java. Type of research used in this research is analytical descriptive research type through qualitative approach. Sources of data used in the form of primary data derived from the results of in-depth interviews of research informants and secondary data in the form of archives and documentation. The technique of selecting informants using purposive sampling.The results of this research indicate that forms of movement made by GenPI  Central Java are very instrumental in helping the government in promoting tourism in Central Java. People who feel the impact of the forms of movement carried out by GenPI in the development of tourism are the people involved and play a direct role in the tourism development program conducted by GenPI. The GenPI movement as community development itself is divided into two, namely creative movements or creative values and commercial movements or commercial values. GenPI has a form of coordination that involves and connects academics, business people, communities, government, and the media both in the movement and in coordination, GenPI divides it into 6 ex-residency areas so that the role given can be evenly distributed throughout the Central Java region.The suggestion that can be conveyed in this research is that the GenPI Central Java needs to consolidate and strengthen its membership in overcoming internal and external problems. Creating good communication in the GenPI Central Java with the outsiders such as the government and the society. The Central Java GenPI should not only move to gather the masses but must pay attention to aspects related to the sustainability of a destination. Innovations must be carried out to support the sustainability of tourism in Central Java by considering community-based aspects. Keywords : Generasi Pesona Indonesia, Tourism, Community Development